RANCANGAN MODUL BIOLOGI PADA MATERI PROTISTA KELAS X SMA - Tri Viana; Zulfarina Zulfarina; Nursal Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The development of science and technology is so rapid, the world ofeducation is required to produce natural resources and quality education. One way toimprove the quality of education is to use teaching materials. The limitations of existinglearning resources in the form of teaching materials specifically for protists make theteaching and learning process less effective and become an obstacle in achieving protistmaterial, moreover the scope of protist material is quite large with a relatively shortduration of protist material delivery. This study aims to determine the potential of thedesign of the biology module on the protist material for class X senior high school. Thisresearch was conducted at the Bina Widya Campus, Riau University in August -November 2020. The design of this module refers to the ADDIE development modelwhere the stages used are only the analysis and design stages. The analysis stage wascarried out by analyzing the 2013 curriculum and analyzing the learning material.Thedesign stage is done by designing learning tools in the form of a syllabus and lessonplans first and then designing modules. Based on the potential analysis of the researchresults, it can be used as a design for biology modules on special material for plant-likeprotists of class X SMA KD. 3.6 Grouping protists based on general characteristics ofthe class and their role in life and KD 4.6 Presenting reports on the results ofinvestigations about the various roles of protists in life.Key Words: Module, Protista